Telaah Konstitusi Check And Balances DPR Atas Hak Prerogatif Presiden Dalam Pengangkatan Pejabat Negara - Yudha Yosephin Tambunan; Kezia Ananda Restu; Marshanda Luad Dahlia; Cindy Valentina Natasya S (Lembaga Pengembangan Kinerja Dosen, 2023)
The Review of the DPR's Check and Balances Constitution on the Prerogative of the President in Appointing State Officials discusses the role of the DPR in limiting the president's prerogative in appointing state officials in Indonesia. The research was conducted using a normative approach with a focus on examining relevant laws and regulations. In practice, there are still deficiencies in the system for appointing state officials in Indonesia, where the DPR is often less active in limiting the president's prerogative and only giving approval without conducting a more in-depth evaluation of candidates for state office. Although efforts have been made to strengthen the mechanism of checks and balances in appointing state officials during President Jokowi's administration, there are still challenges and obstacles that need to be overcome, such as the lack of openness and transparency in the selection of candidates for state officials. Therefore, close collaboration between the government, DPR and civil society is needed in strengthening the check and balance mechanism in the appointment of state officials in Indonesia, in order to create a more transparent, accountable and high integrity appointment system for state officials.